Restructuring proceeding of developers - Mosionek, Krzysztof (Studia Iuridica Toruniensia, 2021)
This article is about of restructuring proceedings of developers, whose primary purpose is to satisfy buyers by transferring ownership of the premises to them. The article discusses in detail the most common restructuring methods and specific instruments for effective restructuring and protection of the rights of purchasers of premises.